If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2 = 2x + 13 Reorder the terms: -2 + 3x = 2x + 13 Reorder the terms: -2 + 3x = 13 + 2x Solving -2 + 3x = 13 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -2 + 3x + -2x = 13 + 2x + -2x Combine like terms: 3x + -2x = 1x -2 + 1x = 13 + 2x + -2x Combine like terms: 2x + -2x = 0 -2 + 1x = 13 + 0 -2 + 1x = 13 Add '2' to each side of the equation. -2 + 2 + 1x = 13 + 2 Combine like terms: -2 + 2 = 0 0 + 1x = 13 + 2 1x = 13 + 2 Combine like terms: 13 + 2 = 15 1x = 15 Divide each side by '1'. x = 15 Simplifying x = 15
| -12x+3=-8x-6 | | (k+4)=7 | | -2(3+4m)=-18 | | 22=-6-2r | | 10-7n=-25 | | y=2.22x+4.40 | | 35=-7(3+t) | | (-3xy)(7xy)= | | 14n+q=rt-4n | | -10+9x=125 | | 3x+48=2x+24 | | 40x+9.6x=644.80 | | 0=-(x-3)(x-3)+1 | | 5.50(h)=71.50 | | 5w-4w+2w=9 | | 3x+9-9(x+1)=2x+5 | | -5/12*27/15= | | 12+5x=68 | | 15y+17=13y+14 | | 2x-6=5x+22 | | 40-14x=21x-100 | | 0.10+0.05(52-x)=4.50 | | 7=6m-2m+3 | | 7x(6+8)=7*6+7x | | 16x-6153=1143 | | 4(4x-7)(2x+7)=0 | | 170+106+17x=1600 | | x+-4+2x=1 | | s-10=20.68 | | 4x-84=9x+3 | | 8-4u=8u-5 | | 86x+9648=48090 |